Effects of Listening to the Holy Qur’an on the Accuracy of the Shooting of Jordan’s Players of the National Shooting Team with an Air Pistol - Ali Abdumajeed Zureigat, Ayed (Dirasat: Human and Social Sciences, 2022)
The study aims to identify the level of accuracy of correction and focus of attention before and after listening to the Holy Quran among the players of the national shooting team, as well as to the differences in the accuracy of correction and focus of attention between the two measurements before and after. To achieve this, the researcher used the experimental method on a sample consisting of (n = 12). Attention concentration test (d2) was used to measure the level of attention concentration of the study sample. The researcher used Surat Al-Raad from the Holy Quran, where the player listens to Surat Al-Raad in the voice of the reciter Abdullah Al-Musa through his headphone. To treat the data statistically, the researcher used arithmetic averages, standard deviations, and (t) test for double samples (paired sample t-Test). The results of the study showed that the accuracy level of correction is (237.08) before listening to the Holy Qur’an and (280.25) from (300) after listening to the Holy Qur’an. The results of the study also indicated that there are statistically significant differences at a significance level (0.05> α) between the two measurements: The pre- and post-focus variable for the variable focus of attention in favor of the post-measurement, and the researcher recommends the need to continue listening to the Holy Quran during training and directly before competitions.